La construcción de la identidad de género en estudiantes de grado noveno del Colegio Atanasio Girardot IED en Bogotá: análisis del discurso visual en autorretratos digitales - Velandia Rubio, Ayaleidy (Universidad Antonio Nariño, 2024)
This study aims to understand how ninth-grade students at Colegio Atanasio Girardot IED express the construction of their gender identity through digital self-portraits and anecdotal narratives. Through the completion of an online questionnaire, 47 responses and 93 digital selfportraits were obtained, which were evaluated using a rubric based on their proximity to or distance from gender stereotypes. The analysis was further enriched by tracking the use of grammatical gender descriptors in the anecdotal narratives and labels.